2007
DOI: 10.1007/s00402-007-0350-7
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Carpal tunnel syndrome in patients who are receiving long-term renal hemodialysis

Abstract: Hemodialysis patients are at considerable risk of developing carpal tunnel syndrome in the wrist with an arteriovenous fistula. Close observation and routine clinical examination is mandatory to prevent further problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 12 publications
0
16
0
5
Order By: Relevance
“…In a report on the association between CTS and A-V fistulas in patients on HD (13), clinical CTS was more frequently diagnosed in the wrist with an A-V fistula; however, electrodiagnostic studies did not indicate any significant association between the frequency of CTS and the A-V fistula or its duration. Such reports raise questions about the validity of electrodiagnostic results in patients with an A-V fistula, because of the discrepancy between the clinical and electrodiagnostic findings.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In a report on the association between CTS and A-V fistulas in patients on HD (13), clinical CTS was more frequently diagnosed in the wrist with an A-V fistula; however, electrodiagnostic studies did not indicate any significant association between the frequency of CTS and the A-V fistula or its duration. Such reports raise questions about the validity of electrodiagnostic results in patients with an A-V fistula, because of the discrepancy between the clinical and electrodiagnostic findings.…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, the electrodiagnostic confirmation of CTS was not associated with the type of dialysis in this study. Many investigators have reported a positive correlation between the frequency of CTS and the duration of HD (3, 5), and have also reported that the side of the A-V fistula could affect the frequency of CTS (12, 13). However, the results of this study do not reveal the relationship between the frequency of electrodiagnostic CTS and the duration of ESKD, dialysis, and the side of the A-V fistula.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of CTS in the wrist where the AV fistula was located did not fulfill the criteria for statistical significance. A relationship between CTS and the AV fistula location has been postulated in many publications [6,13,1618]. The pathomechanism of CTS in hemodialysed patients appears to be complicated.…”
Section: Discussionmentioning
confidence: 98%
“…La prévalence de 30,5% du SCC chez nos patients hémodialysés chroniques concorde avec la série tunisienne de Namazi et al en 2007 (42,7%) [9], alors qu'elle est plus élevée en comparaison avec la série américaine de Gilbert et al en 1988 (9%) [10], et celle Allemande de Schwalb et al en 1996 (16,3%) [11]. Cette variabilité peut être expliquée par la différence de la durée de dialyse dans ces études, grâce à l'amélioration de la survie des patients au fil des années ainsi que par la disparité des critères (cliniques, élecrophysiologiques, ou histologiques) considérés pour le diagnostic du SCC dans les séries.…”
Section: Résultatsunclassified